2015
DOI: 10.1177/1056789515610397
|View full text |Cite
|
Sign up to set email alerts
|

Torsional failure of water-filled carbon nanotubes

Abstract: The failure behavior of water-filled carbon nanotubes under the torsional moment is investigated by molecular dynamics simulations. The computational results indicate that the shear modulus can be slightly increased but the critical buckling angle can be greatly enhanced by the water filling as compared to the empty carbon nanotubes. The enhancement in the critical buckling angle is almost comparable to that induced by the copper filling. However, the critical failure angle of carbon nanotubes decreases with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Buckling experiments on the miniaturized specimens are difficult to conduct since applying appropriately aligned uniform compression loads at the specimen's ends is challenging. The atomistic models (e.g., Shen and Chen, 2006;Ye et al, 2016;Zhang et al, 2017aZhang et al, , 2017b are computationally expensive and therefore, may not be used for design purposes. For these reasons, the engineering science community has always appreciated the analytical modeling of the buckling of micro-and nanosized pillars and beams.…”
Section: Introductionmentioning
confidence: 99%
“…Buckling experiments on the miniaturized specimens are difficult to conduct since applying appropriately aligned uniform compression loads at the specimen's ends is challenging. The atomistic models (e.g., Shen and Chen, 2006;Ye et al, 2016;Zhang et al, 2017aZhang et al, , 2017b are computationally expensive and therefore, may not be used for design purposes. For these reasons, the engineering science community has always appreciated the analytical modeling of the buckling of micro-and nanosized pillars and beams.…”
Section: Introductionmentioning
confidence: 99%
“…CNT is a kind of hollow structure, the mechanical properties of which can be, therefore, modified by encapsulating the metal particles [7][8][9][10], C60 [11][12][13], water [14,15,[16][17][18][19] and other gas molecules [12,20]. By employing molecular dynamics (MD) simulations, Guo et al [7] found that the strength of gold-filled CNT is significantly enhanced in comparison with hollow CNT.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based nano-materials such as carbon nanotube and graphene have been studied on its fracture behaviors and mechanical properties using MD simulation extensively. For carbon nanotubes, Ye et al (2016) investigated the torsional failure of water-filled carbon nanotube and compared its behaviors with empty carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%